Preparation of alkali-soluble polysaccharide from Clausena lansium (Lour.) Skeels and its effects on properties of chitosan-based edible film - Ren, Yuan-Yuan; Fang, Juan-Li; Gong, Rui-Zhi; Xiang, Zi-Ling; Sun, Peng-Peng (Frontiers in Sustainable Food Systems, 2023)
In this study, alkali-soluble polysaccharide from wampee (ASP-W) was prepared and its effect on chitosan-based composite film was investigated. Preliminary characterization of ASP-W showed it was a kind of typical homogeneous polysaccharide, with molecular weight of 1.5×103 KDa. Infrared spectroscopy proved successful combination of ASP-W with chitosan. Meanwhile, composite film exhibited increased thickness, water solubility percentage, swelling ratio and decreased moisture content. In terms of optical transmittance, composite films showed excellent UV barrier capability below 400 nm. Mechanical tests demonstrated tensile strength up to 24.84 MPa at ASP-W 1.5%, elongation at break up to 27.93% at ASP-W 4.5%. Composite films also possessed better barrier properties. Besides, differential scanning calorimeter (DSC) results indicated better thermostability of composite films. DPPH radical scavenging reached to 46.84% at ASP-W 1.5% and hydroxyl radical scavenging peaked at 97.16% at ASP-W 3%. In summary, ASP-W can improve optical, mechanical, barrier, thermal stability and antioxidant properties of chitosan film, which provided a certain reference for the development and utilization of polysaccharide in packaging edible film.